Does management integration improve cross-level clinical coordination? Experience of Catalonia. (30th September 2020) - Esteve-Matalí, L; Vargas, I; Cots, F; Ramon, I; Sánchez, E; Coderch, J; Plaja, P; Vázquez for Gaia, M L
Abstract: Background: Cross-level clinical coordination is a priority for health systems. Evidence suggests that management integration may improve clinical coordination. This study aims to evaluate clinical coordination according to the type of management integration of the area in the Catalan health system. Methods: Cross-sectional study based on the online questionnaire COORDENA-CAT (October-December 2017). Study population: primary and secondary care (acute and long term) doctors of the public Catalan health system. Sample: 3.308 doctors. Outcome variables: experience and perception of clinical coordination across care levels, knowledge and use of coordination mechanisms and related factors. Explanatory variables: area according to type of management (integrated, semi-integrated and non-integrated), demographic, employment characteristics and attitude towards work. Descriptive and multivariate analysis by robust Poisson regression. Results: Better clinical coordination was observed in integrated areas compared to those semi-integrated, mostly in information transfer (PR 0.80 (95%CI 0.74-0.87)) and adequate follow-up of the patient (PR 0.89 (95%IC 0.82-0.97)). No differences were observed between integrated and non-integrated areas. General perception of coordination was higher in integrated areas than in semi-integrated and non-integrated areas (PR 0.73 (95%CI 0.63-0.84) and PR 0.85 (95%CI 0.75-0.97) respectively). Some organizational and interactional factors and the knowledge and use of coordination mechanisms showed also better results in integrated areas. There were common fields for improvement like accessibility between care levels. Conclusions: No differences between integrated and non-integrated areas reveal that management integration is not enough condition to improve clinical coordination. Differences with semi-integrated areas suggest that coordination efforts should be equitable among all the providers of the territory to avoid inequalities in quality of care. Key messages: Management integration does not determine clinical coordination. Cooperation formulas are needed between all territory providers that allow to fix common strategies to improve clinical coordination.